2023
DOI: 10.3389/fncir.2023.1086053
|View full text |Cite
|
Sign up to set email alerts
|

Ventral pallidal regulation of motivated behaviors and reinforcement

Abstract: The interconnected nuclei of the ventral basal ganglia have long been identified as key regulators of motivated behavior, and dysfunction of this circuit is strongly implicated in mood and substance use disorders. The ventral pallidum (VP) is a central node of the ventral basal ganglia, and recent studies have revealed complex VP cellular heterogeneity and cell- and circuit-specific regulation of reward, aversion, motivation, and drug-seeking behaviors. Although the VP is canonically considered a relay and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 292 publications
2
23
0
Order By: Relevance
“…Overall, these results are consistent with BF Npas1 + neurons being involved in limbic basal ganglia circuits related to motivation, reward, stress and sleep-wake control (Luo et al, 2018;Li et al, 2021;Fifel et al, 2022;Morais-Silva et al, 2023;Soares-Cunha & Heinsbroek, 2023).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, these results are consistent with BF Npas1 + neurons being involved in limbic basal ganglia circuits related to motivation, reward, stress and sleep-wake control (Luo et al, 2018;Li et al, 2021;Fifel et al, 2022;Morais-Silva et al, 2023;Soares-Cunha & Heinsbroek, 2023).…”
Section: Discussionsupporting
confidence: 83%
“…An approach that has been productive in defining subpopulations of cerebral cortex GABAergic interneurons (Lim et al, 2018) and subpopulations of GABAergic projection neurons in the basal ganglia (Hernandez et al, 2015; Abecassis et al, 2020; Cui et al, 2021) is the use of developmental transcription factors to serve as markers for specific neuronal populations. This approach has also been fruitful in identifying novel sleep-wake populations in the hypothalamus (Liu et al, 2017) and brainstem (Kirjavainen et al, 2022), but has so far not been applied to the basal forebrain (BF), a key brain region involved in the control of sleep-wake behavior, cortical activation, attention, and motivation (Detari et al, 1999; Zaborszky and Duque, 2003; Brown et al, 2012; Brown and McKenna, 2015; Lin et al, 2015; Morais-Silva et al, 2023) which degenerates in dementia patients (Grothe et al, 2014; Pereira et al, 2020) and is dysregulated in various psychiatric disorders (McNally et al, 2021; Morais-Silva et al, 2023; Soares-Cunha & Heinsbroek 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The NAc is mainly composed of GABAergic MSNs, which account for ~95% of the accumbal neurons, being divided into those that express dopamine receptor D1 (D1-MSNs) or D2 (D2-MSNs) (Gerfen et al, 1990). D1-MSNs project directly to the ventral tegmental area (VTA), forming the direct pathway, while D2-MSNs, together with a subpopulation of D1-MSNs, project to the ventral pallidum (VP), forming the indirect pathway (Kupchik et al, 2015;Soares-Cunha and Heinsbroek, 2023). Different studies have shown that both subpopulations are functionally divergent (Hikida et al, 2010;Kravitz et al, 2012;Lobo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The NAc is mainly composed of GABAergic medium spiny neurons (MSNs), which account for ~95% of the accumbal neurons, being divided into those that express dopamine receptor D1, dynorphin and substance P (D1‐MSNs) or those expressing dopamine receptor D2, enkephalin and adenosine 2a receptor (A2A) (D2‐MSNs) (Gerfen, 1984; Gerfen et al., 1990; Le Moine et al., 1991). These two populations also show anatomical segregation, with a significant proportion of D1‐MSNs projecting directly to the ventral tegmental area (VTA), forming the direct pathway, and with both populations projecting to the ventral pallidum (VP), forming the indirect pathway (Baimel et al., 2019; Gerfen, 1984; Kupchik et al., 2015; Soares‐Cunha & Heinsbroek, 2023). Different studies have shown that both sub‐populations are functionally divergent (Hikida et al., 2010; Kravitz et al., 2012; Lobo et al., 2010).…”
Section: Introductionmentioning
confidence: 99%